Factors influencing response to Botulinum toxin type A in patients with idiopathic cervical dystonia: results from an international observational study. Issue 3 (14th June 2012) - Misra, Vijay P; Ehler, Edvard; Zakine, Benjamin; Maisonobe, Pascal; Simonetta-Moreau, Marion; ,
Abstract : Objectives: Real-life data on response to Botulinum toxin A (BoNT-A) in cervical dystonia (CD) are sparse. An expert group of neurologists was convened with the overall aim of developing a definition of treatment response, which could be applied in a non-interventional study of BoNT-A-treated subjects with CD. Design: International, multicentre, prospective, observational study of a single injection cycle of BoNT-A as part of normal clinical practice. Setting: 38 centres across Australia, Belgium, Czech Republic, France, Germany, The Netherlands, Portugal, Russia and the UK. Participants: 404 adult subjects with idiopathic CD. Most subjects were women, aged 41–60 years and had previously received BoNT-A. Outcome measures: Patients were classified as responders if they met all the following four criteria: magnitude of effect (≥25% improvement Toronto Western Spasmodic Torticollis Rating Scale), duration of effect (≥12-week interval between the BoNT-A injection day and subject-reported waning of treatment effect), tolerability (absence of severe related adverse event) and subject's positive Clinical Global Improvement (CGI). Results: High rates of response were observed for magnitude of effect (73.6%), tolerability (97.5%) and subject's clinical global improvement (69.8%). The subjective duration of effect criterion was achieved by 49.3% of subjects; 28.6% of subjects achieved the responder definition. Factors most strongly associated with response were age (<40 years; OR 3.9, p<0.05) and absence of baseline head tremor (OR 1.5; not significant). Conclusions: Three of four criteria were met by most patients. The proposed multidimensional definition of response appears to be practical for routine practice. Unrealistically high patient expectation and subjectivity may influence the perception of a quick waning of effect, but highlights that this aspect may be a hurdle to response in some patients. Clinical registration number: (NCT00833196 ; ClinicalTrials.gov ).